PENGARUH KUALITAS LAYANAN TERHADAPKEPUASAN NASABAH - L. Anisia Fatsha, 08.05.51.0102; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2013)
The purpose of this study was to analyze the influence of variable tangible, reliability, responsiveness, insurance, and empathy to the credit customer satisfaction BPR Arto Moro Semarang. Samples used in this study of 100 respondents with a sampling technique is purposive sampling. The collected data were analyzed using factor analysis, the formula Cronobachs Alpha, multiple regression analysis, t test. The research results can be concluded that: (1) The results of statistical calculations with multiple linear regression analysis can be shown by the regression equation Y = 0,197 X1 + 0,630 X2 + 0,177 X3 + 0,147 X4 + 0,182 X5. The most dominant factor in influencing customer satisfaction is a variable reliability backed by the highest reliability of regression coefficient (0.630) followed by tangible variables (0.197), empathy (0.182), responsiveness (0.177) and assurance(0.147). (2) Adjusted R Square by 71,2%. While the remaining 28.8% is influenced by variables other than this research model, for example image. (3) The hypothesis that has been done in this study can be concluded that : There are positive and significant between the tangible, reliability responsiveness, insurance, and empathy to the credit customer satisfaction BPR Arto Moro Semarang.Key words: Service Quality, Customer Satisfaction